Analysis of Sidewalk Comfort Level Based on Width, Cleanliness, Surface Condition, Lighting, and Availability of Signage and Directional Indicators on Sudibyo Street Sidewalks in Tegal City - Ulhaq, Dhiya; Basfian, Muhammad Fahri; Ayuningtyas, Nurina Vidya; Brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Sidewalks are essential for facilitating pedestrian movement and promoting sustainable transportation in urban areas. On Kapten Sudibyo Street in Tegal City, which serves as a main access route to Kardinah Hospital, the sidewalks currently do not meet adequate safety and comfort standards. Problems such as uneven surfaces, reduced width, poor maintenance, and obstructions like illegal parking and public facilities hinder pedestrian comfort and accessibility. This study aims to assess the comfort level of these sidewalks, focusing on factors including width, cleanliness, surface condition, lighting, and signage. Using qualitative method with observations and Guttman-scale surveys distributed to 200 respondents, mainly local students who frequently use the sidewalks, the research analyzed how these factors impact perceived comfort. The results reveal a generally low comfort level, with 72% of respondents expressing dissatisfaction due to poor conditions of the sidewalk. Key recommendations include widening sidewalks to a minimum of 200 cm, repairing uneven surfaces, maintaining cleanliness, upgrading lighting, and providing clear signage. Additional measures involve relocating obstructive public facilities and enforcing regulations against illegal parking to enhance accessibility and safety. These improvements are crucial for creating a more inviting and functional pedestrian space, encouraging walking as a mode of transport, and contributing to a healthier urban environment.